Strategy of antisense oligonucleotides – actual state of art in advanced clinical studies on therapy of selected neoplastic diseases - Stec-Michalska, Krystyna (Contemporary Oncology/Współczesna Onkologia, 2000)
Modulation of translation process and regulation of protein biosynthesis by means of antisense oligonucleotides lay the foundation for new therapeutic strategies, among others against neoplastic diseases. The aim of this account was the presentation of molecular basis of antisense strategy, targeted against Bcl-2 protein. This protein, being expressed by bcl-2 gene, regulates the cell apoptosis and influences the uncontrolled cell proliferation. Below there is presented the state of art in clinical studies of application of antisense oligonucleotide phosphorothioates in combating those neoplastic diseases where the level of Bcl-2 is recognised as the independent key-marker of cancer progression.